Matrix Gla Protein Promotes the Bone Formation by Up-Regulating Wnt/β-Catenin Signaling Pathway - Zhang, Jie; Ma, Zhenrong; Yan, Kang; Wang, Yong; Yang, Ya; Wu, Xiang (Frontiers in Endocrinology, 2019)
Objective: Studies suggest that matrix Gla protein (MGP) is associated with osteoporosis. However, the precise mechanism through which MGP regulates bone metabolism is not fully understood. The purpose of this study was to clarify the role of MGP in bone metabolism. Methods: The MGP gene in MG63 cell line was knocked down using shRNA. Cell Counting Kit-8 assay was used to detect the proliferation of MG63 cells. Moreover, the differentiation and mineralization of MG63 cells were measured through alkaline phosphatase staining and Alizarin Red S staining. Western blotting and quantitative reverse transcription-polymerase chain reaction were conducted to detect the protein and mRNA levels of components of the Wnt/β-catenin signaling pathway, such as Wnt3a, β-catenin, and Runx2. Transgenic (MGP+) mice were used to detect the effects of MGP in vivo. Results: The Cell Counting Kit-8 assay suggested that upregulated MGP could promote the proliferation of MG63 cells, whereas its downregulation inhibited proliferation. The alkaline phosphatase assay and Alizarin Red S staining showed that overexpressed MGP led to prominently upregulated differentiation and mineralization of MG63 cells. Conversely, knockdown of MGP decreased the levels of differentiation and mineralization. Western blotting and quantitative reverse transcription-polymerase chain reaction showed that overexpression of MGP upregulated Wnt3a, β-catenin, and Runx2. In contrast, knocking down MGP reduced their transcriptional levels. In vivo, overexpression of MGP inhibited the decrease in bone mineral density induced via ovariectomy in the femur, and significantly prevented bone volume fraction, trabecular number, BV/TV and TbTh to decrease. In addition, it increased the levels of estradiol in sera. Conclusion: The findings of this study suggest that the promotion of osteoblast proliferation, differentiation, and mineralization by MGP may be a mechanism to prevent osteoporosis. Furthermore, the results show that MGP promoted the osteogenic effects via the Wnt/β-catenin signaling pathway.